PALINOLOGíA DE LA FORMACIÓN MELO (PÉRMICO INFERIOR) EN ARROYO SECO, DEPARTAMENTO RIVERA, URUGUAY. PARTE V: GRANOS DE POLEN, ACRITARCAS E INCERTAE SEDIS (Ameghiniana, 2014)
The last part ofthe palynological study of the Early Permian Melo Formation at Arroyo Seco, Rivera Department, Uruguay, is presented. Fifty one species of pollen grains, fresh water algae, acritarchs and Incertae sedis are treated systernatically. The following species are reported in the Permian of Uruguay for the first time: Potonieisporites barrelis Tiwari, Cannanoropollis janakii Potonié y Sah, Limitisporites hexagonalis Bosé y Maheshwari, Scheuringipollenites circularis Césari, Archangelsky y V. de Seoane, S. minimus (Burjack) Oias Fabricio, Protohaploxypinus goraiensis (Potonié y Lele) Hart, P hartii Foster, Striatopodocarpites sp. cf. S. rarus (Bharadwaj y Salujha) Balme, vittatina latericostata Menéndez, v fosciolota (Balme y Hennelly) Bharadwaj, Tiwariasporites simplex (Tiwari) Maheshwari y Kar, Marsupipollenites triradiatus Balme y Hennelly, Cycadopites caperatus (Luber y Walts) Han, Granulatasporites pastillus(Samoilovich) Hart, Botryococcus braunii Kützing, Cymatiosphaera gondwanensis (Tiwari) Backhouse, Michrystridium fragile Oeflandre and M. sp. cf. M. teichenii Sarjeant. The stratigraphic range of palynomorphs suggests a late Sakmarian-Artinskian age for the assemblage.